Exchange rate exposure refinement approach on large non-financial firm’s share return in selected Asian countries / Jaratin Lily - Lily, Jaratin (2018)
The purpose of this study was to investigate the stylised exchange rate exposure among large non-financial firms on the selected Asian economies (Indonesia, Malaysia, Philippines, Thailand, Bangladesh, Pakistan, Sri Lanka and Vietnam). Other than relationship assumptions (symmetric, asymmetric and time varying), this study provided an insight how market thinness affects the efficiency of exchange rate exposure model. This study applied different types of methods namely the Autoregressive Distributed Lag (ARDL), the Nonlinear Autoregressive Distributed Lag (NARDL) and a time-varying coefficient approach with GARCH (1,1) specification. Additionally, the Dimson-Fowler-Rorke (DFR) method was applied to correct bias Ordinary Least Squares (OLS) market betas. The findings mainly support the exchange rate exposure theory indicating that exchange rate is one of important factors in decision-making policy. Even though, symmetric relationship assumption is still valid, examining the exposure from different approaches such as asymmetric and time varying is important to explain or weaken the exchange rate exposure puzzle. In addition, refinement in existing exchange rate exposure model at a certain extent has improved the efficiency of the existing exposure model. Furthermore, sample countries especially in Indonesia, Vietnam and Malaysia remained supported by an asymmetric exchange rate exposure with a positive exchange rate shocks (a weaker home currency) having a stronger effect on share returns, as compared to a negative exchange rate shocks (a stronger home currency).